2013
DOI: 10.1001/jamaneurol.2013.165
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Clinical and Molecular-Pathological Profile of Gerstmann-Sträussler-Scheinker Disease Associated With a NovelPRNPMutation (V176G)

Abstract: This case report from the Australian National Creutzfeldt-Jakob Disease Registry concerns a 61-year-old British-born woman with no history of neurodegenerative disorder in first-degree relatives. Rapidly progressive dementia, altered behavior, and cerebellar ataxia dominated the clinical picture in the period immediately following minor elective surgery, with death 1 month later in an akinetic-mute state. Brain histopathological examination revealed neuronal loss, scant foci of spongiform change, and diffuse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…Brain MRI typically shows cerebellar or global atrophy, and FLAIR or DWI hyperintensitites similar to those characteristic of sJCD are uncommon [Krasnianski et al, 2016;Vitali et al, 2011], although the EUROJCD study, found basal ganglia hyperintensities on FLAIR or DWI MRI in 30% of cases [Kovacs et al, 2005]. White matter hyperintensities are occasionally observed, but have also been reported in sJCD and other gPrD (such as gJCD due to the E196K mutation) [Schelzke et al, 2011;Simpson et al, 2013;Webb et al, 2008].…”
Section: Genetic Prion Diseases Usually With Slower Progressionmentioning
confidence: 98%
“…Brain MRI typically shows cerebellar or global atrophy, and FLAIR or DWI hyperintensitites similar to those characteristic of sJCD are uncommon [Krasnianski et al, 2016;Vitali et al, 2011], although the EUROJCD study, found basal ganglia hyperintensities on FLAIR or DWI MRI in 30% of cases [Kovacs et al, 2005]. White matter hyperintensities are occasionally observed, but have also been reported in sJCD and other gPrD (such as gJCD due to the E196K mutation) [Schelzke et al, 2011;Simpson et al, 2013;Webb et al, 2008].…”
Section: Genetic Prion Diseases Usually With Slower Progressionmentioning
confidence: 98%
“…The EuroCJD study, however, reported basal ganglia FLAIR or DWI hyperintensities in 30% of cases; other studies noted FLAIR or DWI abnormalities, such as cortical ribboning or deep nuclei hyperintensities (typical for sCJD) to be very uncommon (Vitali et al 2011;Krasnianski et al 2016). White-matter hyperintensities have occasionally been reported in GSS as well as sCJD and other gPrDs (such as gCJD owing to the E196K mutation), although it is not often clear whether the white matter changes result from the primary prion disease or to other comorbidities (Webb et al 2008;Schelzke et al 2011;Simpson et al 2013).…”
Section: Gerstmann -Strä Ussler -Scheinker (Gss)mentioning
confidence: 99%
“…Parallel to this particular PrP deposition, pathological features characteristic of other neurodegenerative diseases such us parkinsonism or Alzheimer’s disease have been observed in some GSS patients [ 5 ]. Indeed, an increase in hyperphosphorylated Tau is frequently observed in the pathological analysis of brains from GSS patients carrying PRNP mutations P102L [ 10 ], P105L [ 11 ], A117V [ 12 ], V176G [ 13 ], F198S [ 14 , 15 ], Q217R [ 16 , 15 ] and Y218N [ 17 ]. Although it has been shown that PrP C with the P102L mutation display an increased binding to Tau [ 18 ], the role of these point mutations in the development of neurofibrillary degeneration is unknown.…”
Section: Introductionmentioning
confidence: 99%